Comparative biology of test species. - Calabrese, E J (1988)
This paper assesses the capacity of animal models to predict human response to carcinogenic agents with consideration for the heterogeneity of humans. It is widely accepted that human susceptibility to toxic substances, including carcinogens, is highly variable. Conventional rodent models are usually highly inbred and valued for their ability to display characteristic homogeneity. Current practice assumes that the homogeneity of response to toxic agents, including carcinogens, in the rodent model will be representative of humans. The issue then becomes, To which of the broad spectrum of human responses are specific animal models likely to be related? This paper examines the extent of human heterogeneity over a broad range of biochemical characteristics (e.g., aryl hydrocarbon hydroxylase activity, epoxide hydrase activity, beta-glucuronidase activity, debrisoquine hydroxylation, DNA-adduct formation) with emphasis on those biochemical characteristics that affect responses to carcinogens. Examples are presented to compare the heterogeneity of selected animal models for these biochemical characteristics as they relate to the spectrum of human responses noted above. The paper presents a theoretical perspective for determining to which part of the human population response spectrum common animal models are most likely to be extrapolated.